Comparative Genomic Analyses Reveal Potential Factors Responsible for the ST6 Oxacillin-Resistant Staphylococcus lugdunensis Endemic in a Hospital - Chang, Shih-Cheng; Lin, Lee-Chung; Lu, Jang-Jih (Frontiers in Microbiology, 2021)
Oxacillin-resistant Staphylococcus lugdunensis (ORSL) is considered a life-threatening isolate in healthcare settings. Among ORSL clones, ST6-SCCmec II strains are associated with an endemic spread in hospitals. We analyzed the complete genome of ORSL CGMH-SL118, a representative strain. Results revealed that this strain contained three MGEs (two prophages and one plasmid) other than the SCCmec II element, which showed remarkable differences in genome organization compared to the reference strains from NCBI. Eight multidrug-resistant genes were identified. All but blaZ were carried by MGEs, such as the SCCmec II element (mecA, ant (9)-Ia and ermA) and the prophage φSPbeta (aac (6’)-aph (2’), aph (3’)-III, and ant (6)-Ia), indicating that MGEs carrying multidrug-resistant genes may be important for ST6 strains. The prophage φSPbeta contains a virulence factor, sasX, responsible for the pathogenesis of Staphylococcus aureus. A phage-mediated resistant island containing fusB (SlRIfusB-118) was found near φSPbeta, which was highly homologous to type III SeRIfusB-5907 of S. epidermidis. In contrast with previous studies, over 20% of ST6 isolates showed a fusidic acid-resistant phenotype, suggesting that phage-mediated intraspecies transmission of resistant islands may become an important issue for ST6 strains. Among the 50 OSSL and 18 ORSL isolates in this study, ORSL showed similar drug-resistant genes and phenotypes as CGMH-SL118. The comparative genomic analyses highlight the contribution of MGEs in the development and dissemination of antimicrobial resistance in ST6 strains, suggesting that resistance determinants and virulence factors encoded by MGEs provide a survival advantage for successful colonization and spread in healthcare settings.